Max Warren en sy sewe reëls vir ’n dialoog tussen Christene en nie- Christene. - Meiring, PGJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
Max Warren and His Seven Rules for Dialogue Between Christians and non- Christians In 2004 the centenary of Max Warren, one of the greatest all round Christian leaders and missionary thinkers of his time, was celebrated. In South Africa, too, Warren’s life and work had great impact. The author indicates how Warren’s thinking about the dialogue between Christians and non-Christians in the 1960s can serve us today in a country where this dialogue has become a matter of extreme importance. Warren’s seven principles for dialogue – and their relevance for our day – are re-examined. The principles are: acceptance of our common humanity, the principle of divine omnipresence, accepting the best in other religions, identification, courtesy, interpretation, and expectancy.